Association Of Allelic Polymorphisms Of Pro-Inflammatory Cytokine Genes With The Severity Of Immune Microthrombovasculitis - Matkarimova Dilfuza Saburovna (International Journal of Medical Science and Public Health Research, 2025)
Purpose of the study: To assess the role of the polymorphic variant of the TNF-α gene (rs1800629) VEGFA (rs2010963) in the development of a severe course of immune microthrombovasculitis. Material and methods: The study included 75 patients with IMTV (main group) aged 16 to 80 years and 73 conditionally healthy individuals (comparison group) without pathology of the hemostasis system, comparable in age and gender with the main group. Detection of polymorphic variants of genes TNF-α (rs 1800629) and VEGFA (rs2010963) was carried out by SNP-PCR. Results and discussion: Differences in the frequency of occurrence of the mutant genotype of the mutant genotype G/G (χ2>3.84; P<0.05) of the polymorphic variant of the VEGFA gene (rs2010963) were established depending on the severity of IMTV, which allows clinicians to determine it as a genetic predictor of severe disease.